Pelatihan Penerapan Keterampilan Dasar Mengajar Bagi Calon Guru - Mailani, Ikrima (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
Islamic Religious Education plays a crucial role in shaping the character of individuals and societies through religious values. At Kuantan Singingi Islamic University, special attention is given to the development of prospective Islamic Religious Education teachers. A community service program titled